DOI: 10.18174/499579
|View full text |Cite
|
Sign up to set email alerts
|

Urbanizing flows : growing water insecurity in peri-urban Kathmandu Valley, Nepal

Abstract: The codified and written law applicable to the whole kingdom of Nepal Nani :Term that refers to a younger sister Pani nacalne choi chito halnu parne : Untouchable castes Pani nachalne : Those with whom higher castes were not to share water (to drink or use water offered or touched by them Pani nachalne choi chito halnu naparne : Impure but touchable castes Raikar : It denoted the crown-land or state land until 1950. Since then raikar land denotes an individual's private land. Rajkulos : Royal canals Ropani : U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 138 publications
0
15
0
Order By: Relevance
“…The chemical, microbiological, and physical parameters at Sundarijal were within acceptable levels according to the Bagmati Basin Water Management Strategy and Investment Program guideline [ 8 , 9 ]. A previous study conducted in this region reported that these upstream sites of the river are minimally affected by anthropogenic activities [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chemical, microbiological, and physical parameters at Sundarijal were within acceptable levels according to the Bagmati Basin Water Management Strategy and Investment Program guideline [ 8 , 9 ]. A previous study conducted in this region reported that these upstream sites of the river are minimally affected by anthropogenic activities [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to an inadequate water supply, untreated water from this river is used by many inhabitants [ 4 , 5 ] for various purposes, including for irrigation [ 6 ], cleaning of freshly harvested crops products [ 7 ], and domestic use [ 8 ]. Moreover, uncontrolled population growth and unplanned urbanization have led to most sewage and solid waste from urban areas directly discharging into rivers [ 9 ]. Therefore, the presence of diverse groups of waterborne pathogens in this river water is likely high [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periurban areas are widely growing in importance and geographical spread. There is no uniformly accepted definition of the word “periurban” (Gomes and Hermans, 2018; Singh and Narain, 2020; Shrestha, 2019), but it broadly refers to spaces in transition that combine features of both rural and urban environments. They are located usually at the periphery of cities, providing resources for urban expansion and receiving urban wastes, though scholars caution against purely place - based definitions of periurban, highlighting instead the importance of underlying institutional contexts (Iaquinta and Drescher, 2000; Singh and Narain, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The negotiated approach has been tried as one approach to engage communities in dialogue with state agencies, as demonstrated in parts of periurban Kolkatta, India and Khulna, Bangladesh (Gomes et al , 2018; Gomes and Hermans, 2018). Given the diversity and social and economic heterogeneity in periurban settings, however, studies point to the limited relevance of the concept of “community resilience”, critiquing the notion of “community” as a homogenous, monolithic whole (Shrestha, 2019). This is because of the huge diversity and inequality among those who inhabit periurban spaces.…”
Section: Introductionmentioning
confidence: 99%